PUBLIC HEALTH ORGANIZATION IN MEXICO - QUINONES, MARIO (Rockefeller Foundation, CD MEXICO, DF, MEX, 1914)
Widal tests were conducted on 3147 blood samples sent to the laboratory for Wassermann tests Of the 3147, a total of 432 (137%) gave positive Widal reactions at a dilution of 1-80 or higher 130 reacted at 1-80; 174 at 1-120 and 24 at 1-640
AM J PUBL HEALTH
Keywords: PUBLIC, HEALTH, ORGANIZATION, MEXICO; CIENCIAS MEDICAS; SALUD PUBLICA